Bartonella quintana in Body Lice and Head Lice from Homeless Persons, San Francisco, California, USA - Bonilla, Denise L. (Centers for Disease Control and Prevention, 2009)
Bartonella quintana is a bacterium that causes trench fever in humans. Past reports have shown Bartonella spp. infections in homeless populations in San Francisco, California, USA. The California Department of Public Health in collaboration with San Francisco Project Homeless Connect initiated a program in 2007 to collect lice from the homeless to test for B. quintana and to educate the homeless and their caregivers on prevention and control of louse-borne disease. During 2007–2008, 33.3% of body lice–infested persons and 25% of head lice–infested persons had lice pools infected with B. quintana strain Fuller. Further work is needed to examine how homeless persons acquire lice and determine the risk for illness to persons infested with B. quintana–infected lice.